Trace xenon detection in helium environment via laser-induced breakdown spectroscopy. Issue 4 (24th March 2021) - Burger, M.; Garrett, L.; Burak, A. J.; Petrov, V.; Manera, A.; Sabharwall, P.; Sun, X.; Jovanovic, I.
Abstract : We assess the sensitivity of LIBS for trace xenon detection in a helium buffer and its suitability for online monitoring of reactor fuel integrity. Abstract : There is significant motivation to develop and deploy novel nuclear reactor designs to deliver improved performance, safety, and economics for nuclear energy. In gas-cooled fast reactors that use helium as the primary coolant, the presence of xenon could indicate the onset of the fuel failure. We performed a feasibility study using single-pulse laser-induced breakdown spectroscopy to assess the sensitivity for trace xenon detection in a helium buffer of the pressure of 1.25 bar at room temperature. Under these experimental conditions, parametric optimization of recording parameters has ultimately led to the xenon detection limit of about 0.2 μmol mol −1 for 10 4 laser shots. The results show promise for the use of this technique for online monitoring of reactor fuel integrity, and motivate studies for the development of a compact measurement system that could be integrated with the reactor's primary helium-cooling loop.